JavaScript complete grandmaster 2022. - Matthew, Clyde (Packt Publishing, 2022)
Become a Grandmaster in JavaScript by starting with the foundation level and moving toward advanced level in JavaScript. About This Video Latest JavaScript (ES6/ES7/ES8/ES9/ES10/ESNext) covered in this course Learn how to use JavaScript and what it can do for you Become an independent web developer from beginning to expert (advanced +) In Detail JavaScript is the #1 scripting language of the web, where a lot of the dynamic and styled content is handled by JavaScript in the background. But before using this language to create dynamic websites, you need to have a firm grasp of how it works behind the scenes. You will learn "why" things work and not just "how". Understanding the fundamentals of JavaScript is important as it will allow you to write more complicated code. And trust me, every programming encounters bugs, and without understanding the fundamentals, you will be totally lost. By the end of this course, you will be able to "speak" JavaScript by gaining an understanding of how the browser uses it; what variables, objects, and functions are; what different data types there are; and how to manipulate content on a website. We will dig deeper and create our own dialog methods from scratch. You will learn about the arrow syntax, Math.random() function, looping through objects and arrays, and working with dates. We will look at prototypes, JS Engines, the Execution Stack, and a whole bunch more! Through practical examples, this course helps you understand JavaScript piece by piece. And we will use the latest and best features of JavaScript along the way so you can stay ahead of the pack. Audience This course is for beginners and is aimed at people new to the world of web design. No previous JavaScript experience is necessary. This course is for someone wanting to be a professional, an expert, and confident in using JavaScript to create complex and impressive websites.